Proof of Kepler's Laws through the Lens of Newtonian Dynamics - Amitabh Kumar (International Journal of Sustainable Applied Sciences, 2024)
At the beginning of the 17th century, Johannes Kepler developed the laws of planetary motion, which became fundamental to understanding the motion of celestial bodies. These principles have been crucial in forming our knowledge of the solar system and help us comprehend how planets orbit the Sun in elliptical orbits. Although Kepler's laws were derived from empirical observations, Isaac Newton's laws of motion and universal gravitation provided a solid theoretical foundation. This research article examines the evidence for Kepler's laws from a Newtonian dynamics perspective, highlighting the harmonious relationship between Kepler's observational discoveries and Newton's mathematical principles.